Advances in immunology. - Dixon, Frank J. (Frank James), 1920-2008 (Advances in immunology., 1993)
For 30 years, this esteemed serial has provided students and researchers with the latest information in Immunology. You can continue to rely on Advances in Immunology to provide you with critical reviews that examine subjects of vital importance to the field through summary and evaluation of current knowledge and research. The articles stress fundamental concepts, but also evaluate the experimental approaches. Each volume of Advances in Immunology contains a subject index as well as the contents of recent volumes. Each chapter includes references. Researchers and students in microbiology, genetics and immunocology will use this invaluable serial to stay updated on the latest advances for years to come. Key Features * Advances in Immunology will keep you informed on such broadly defined subjects as: * Immunochemistry * Antibody synthesis * Biological action of antibodies * Immunological unresponsiveness * Mechanisms in innate and acquired immunity not involving antibodies * Specialized immunological techniques.